PENGARUH KINERJA KEUANGAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, DAN KEBIJAKAN UTANG TERHADAP NILA PERUSAHAAN : STUDI KASUS PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rahayu, Luluk Atiqah Duwi; Kurniawati, Lintang (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of company financial performance, company growth, and debt policy on company value. This research is a quantitative research. The type of data used in this study is secondary data. The population in this study is property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique uses the purposive sampling method according to the criteria that have been determined and 80 final samples are obtained. The data analysis method used is a multiple linear regression analysis model. The results of the study show that the variables of company performance and debt policy have an effect on the company's value, while the company's growth has no effect on the company's value